The Metaphorical Use of Language in Deuterocanonical and Cognate Literature - Witte, Markus,Behnke, Sven (De Gruyter, 2015)
Metaphors are a vital linguistic component of religious speech and serve as a cultural indicator of how groups understand themselves and the world. The essays compiled in this volume analyze the use, function, and structure of metaphors in Jewish writings from the Hellenistic-Roman period (including the works of Philo and the texts of Qumran), as well as in apocryphal early Christian texts and inscriptions.
Description based on publisher supplied metadata and other sources
Keywords: Konferenzschrift; Metapher; Religiöse Sprache; Frühjudentum; Frühchristentum; Literatur; Bible; Christian literature; Early – History and criticism; Jewish religious literature – History and criticism; Metaphor in literature; Metaphor in the Bible